Co-composting of kitchen waste and sawdust with addition of biochar - Samsudin, Mohd Hafif (2017)
Composting is a feasible way to convert kitchen waste into valuable products, as a better method in kitchen waste management. Kitchen waste contains high nitrogen content with easily degradable organic matter, hence making it suitable for the composting process. The improvement of the composting process was carried out with the application of biochar to enhance the physicochemical characteristics of composting process and improve the bacterial community. In this study, the effect of biochar derived from coconut shell on the co-composting process of kitchen waste and sawdust in a small scale (120 L composter) was investigated. Kitchen waste (60 L, v/v) collected from Taman Sri Serdang residential area was mixed with sawdust (60 L, v/v) and added with biochar (4%) and matured compost (4%). Temperature, pH, moisture content and aeration rates were monitored continuously throughout the co-composting process. It was found that the co-composting with addition of biochar improved the physicochemical characteristics of the compost. The co-composting of kitchen waste and sawdust with biochar addition was sustained in the thermophilic phase for longer time (14 days) as compared to compost without biochar, with maximum temperature of 71.5 ℃. The C/N ratio of compost with biochar addition was reduced from 33.7 to 11.8, while the contents of nitrogen, phosphorus and potassium were 3.3%, 3.2% and 1.2%, respectively. Higher nitrogen content was obtained from the co-composting with biochar addition as compared to the co-composting without biochar. Biochar appeared to trap the nitrogen from being released. Biochar addition also promoted the changes in bacterial community composition throughout the co-composting process. In order to elucidate the changes of bacterial community structure during co-composting process, polymerase chain reaction-denaturing gradient gel electrophoresis (PCR-DGGE) analysis was carried out. More DGGE bands appeared in the co-composting with addition of biochar, indicating higher bacterial diversity as compared to the co-composting without biochar addition. The results also showed the presence of Proteobacteria as the dominant phylum for both treatments with and without biochar addition. Further analysis was then carried out using Illumina MiSeq sequencing to elucidate the shift of bacterial diversity during the co-composting process. At the end of the co-composting process, six major phyla including Firmicutes, Gemmatimonadetes, Proteobacteria, Actinobacteria, Bacteriodetes and Chloroflexi for both experiments were detected. The most abundant Actinobacteria phylogeny was found at the end of the co-composting process with biochar addition which may function in the degradation of the lignocellulolytic compound contained in the sawdust. In order to support the results obtained, scanning electron microscopy (SEM) analysis was conducted to observe the morphological changes of the bacteria on the surface of biochar and chicken bone. The analysis revealed different bacterial morphology dominated at mesophilic, thermophilic and curing phases of the co-composting. These bacteria appeared to influence the physicochemical characteristics of compost, including temperature and pH. It is therefore suggested that biochar addition reduced nitrogen loss and induced bacterial community composition during the co-composting process.